(untitled) (Eureka Journal of Business, Economics & Innovation Studies, 2026)
This article analyzes the issues of assessing the economic efficiency of using "green energy" in the energy sector and its forecasting. In the course of the research, the role of renewable energy sources in the energy system, their economic and environmental benefits, and their importance in diversifying the country’s energy balance were studied. The indicators of electricity generation and use of renewable energy sources for 2020-2024 were analyzed. Also, the ARIMA model was used based on time series analysis to develop forecast indicators until 2030. The results of the study show that the development of renewable energy sources is of great importance in increasing economic efficiency in the energy sector, ensuring energy security, and strengthening environmental sustainability. At the same time, it is substantiated that it is possible to ensure sustainable development of the energy sector through state policy on the development of green energy, improving the investment climate, and introducing innovative technologies.